ANALISA USAHA BUDIDAYA UDANG VANAME (Litopenaeus vannamei) AIR TAWAR DI KOLAM BUNDAR DENGAN SISTEM RESIRKULASI AIR - Faisol Mas'ud; Tri Wahyudi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2018)
The decline in vaname shrimp farming land in Lamongan Regency, East Java is influenced by the conversion of cultivation land into residential areas and industrial estate development so that it requires a breakthrough in aquaculture technology, one of which is by utilizing home garden for fish farming using tarpaulin ponds. This study aims to determine the feasibility of the cultivation of vaname shrimp in a circular pond with a recirculation system. The research method is an experimental method and qualitative descriptive in the cultivation of vaname shrimp in a circular pond with recirculation and non-recirculation systems. The results showed that the first pool showed better growth and survival of 10.1 gr / head and 76% with a total production value of Rp.2.470.000; while the second pool shows a lower growth and survival rate of 8.7 gr / head and 62% with a total production value of Rp. 1,620,000. Business feasibility has not been achieved in the first cycle because the value of small production is influenced by the growth of shrimp, low life graduation and lack of duration of maintenance, the simulation of business feasibility can be achieved in 3-4 maintenance cycles.